1991
DOI: 10.1115/1.2919915
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Voltage Polarity on Ice Accretions on Short String Insulators

Abstract: The present study investigated the effect of voltage polarity on ice deposits accumulated on a short-string of porcelain insulators from 85 μm supercooled droplets in a cold room maintained at a temperature of −12°C. The air velocity and the liquid water content were 3.3 m/s and 2.0 g/m3, respectively. Under these growth conditions, the type of ice accretion was hard rime with a density of 0.87 g/cm3 and the highest probability of flashover occurrence. With an applied voltage of 15 kV per insulator unit, corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…During the cooling period, some weak motion could be observed near the electrodes at the beginning of cooling. Once the water was frozen, the surface of the ice remained uneven and the ice bulk contained a lot of microscopic encapsulations created by water movement, which is also reported in other studies [30] [59] (Fig. 4-2a).…”
Section: Effect Of Cooling Ratesupporting
confidence: 79%
See 2 more Smart Citations
“…During the cooling period, some weak motion could be observed near the electrodes at the beginning of cooling. Once the water was frozen, the surface of the ice remained uneven and the ice bulk contained a lot of microscopic encapsulations created by water movement, which is also reported in other studies [30] [59] (Fig. 4-2a).…”
Section: Effect Of Cooling Ratesupporting
confidence: 79%
“…Under the experimental conditions of this study, ice accretion showed only small protuberances in the absence of an electric field, whereas in the presence of electric fields higher than 10 x10 The presence of an electric field influences also the growth of icicles as the water drop hanging from the tip of the icicle is deformed and elongated under enhanced field strength [31]. On the one hand, cooling effects are produced by decrease in drop diameter and increase in ionic wind, whereas, heating effects are created on the other hand by the conduction current.…”
Section: Influence Of Electric Field On Ice Formationmentioning
confidence: 69%
See 1 more Smart Citation
“…Their length varies between 3 cm [45] and 5 cm [46]. hi [47] Field observations over several winter periods were reported in [41]. An average value of 5 mm was observed for the thickness of ice, whereas the length varied widely depending on the type of insulator and the severity of the freezing rain conditions.…”
Section: Geometric Form Of Icicle Tipmentioning
confidence: 99%
“…The presence of a highly conductive water film increases the voltage across the air gaps. These air gaps are formed during the growth period of icicles due to the activity of corona discharge at the icicle tips [5], [19], [20], [69], [70], [71]. If the electric field across the air gaps is high enough, corona discharges will appear across them.…”
Section: Flashover Mechanisms Of Ice-covered Insulatorsmentioning
confidence: 99%